Leasing and credit risk - Grenadier, Steven R. (Journal of Financial Economics, 1996)
Despite empirical evidence pointing to a strong similarity between lease contracts and junk bonds, the theoretical modeling of equilibrium lease determination has been confined primarily to default-free leases. This paper provides a unified framework for determining the equilibrium credit spread on leases subject to default risk. The model is flexible enough to be applied to a wide variety of real-world leasing structures, including security deposits, required up-front prepayments, embedded lease options, leases indexed to use, and lease credit insurance contracts.